1992
DOI: 10.1073/pnas.89.8.3586
|View full text |Cite
|
Sign up to set email alerts
|

In vivo labeling of L-type Ca2+ channels by fluorescent dihydropyridines: evidence for a functional, extracellular heparin-binding site.

Abstract: We have synthesized and charted fluorescently labeled dihydropyridines (DHos) as probes for L-type Ca2+ channels. Racemic as well as (+)-and (-)-1,4-dihydro-2,6-dlmethryl4-(2-trifluoromethylphenyl)-3,5-pyrdlhncrboxylic acid 2-(aminoethyl)ethyl ester hydrochlorides were coupled to boron dipyrromethane (Bodipy) derivatives. (4,4-Diluoro-5,7-dlmethyl-4-bora-3a,4a-diaza)-3-(s-andaceuepropn add (DMBodipy)-DHP and (4,4-difluoro-7-styryl-4bora-3a Radloligand Biding. Rabbit skeletal muscle transversetubule or guinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 41 publications
(26 reference statements)
4
49
1
Order By: Relevance
“…The decrease of fluorescent DHP binding found in our study could reflect a decrease in the expression of L-type Ca 2+ channels rather than a post-transductional change that would result more in a change in ligand affinity [28]. Thus, the decrease of depolarisation-induced Ca 2+ signal and contraction could be attributed to the decrease of CaV1.2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…The decrease of fluorescent DHP binding found in our study could reflect a decrease in the expression of L-type Ca 2+ channels rather than a post-transductional change that would result more in a change in ligand affinity [28]. Thus, the decrease of depolarisation-induced Ca 2+ signal and contraction could be attributed to the decrease of CaV1.2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…It has previously been shown that ligandchannel complexes are destabilized when free Ca*' is reduced below micromolar concentrations, resulting in a time-and temperature-dependent ligand dissociation, that is determined by the conversion rate of the channel to a very low affinity binding state [24]. This process is reversed by readdition of Ca*' [22,24] and the conversion rates, monitored by ligand dissociation from the low affinity state, have been suggested to reflect Ca*' dissociation from the channel [27]. In order to compare the conversion rate constants of a, and a# we performed kinetic experiments where dissociation of (+)-[3HJisradipine binding was induced by reducing the free Ca*' concentration below 10 nM by the addition of 10 mM EDTA.…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of ␣ 1 -DHPR-Cardiac membrane preparations (10-g each) from TGS100A1 and control mice were incubated with 30 nM DM-BODIPY-dihydropyridine (Molecular Probes D-7443) (17) for 60 min at room temperature in equilibration buffer composed of 20 mM HEPES, pH 7.0, 150 mM NaCl, 1 mM EDTA, and 0.5% Tween 20. Samples were centrifuged at 100,000 ϫ g for 20 min, washed three times with equilibration buffer, and resuspended in 1 ml of the buffer.…”
Section: Methodsmentioning
confidence: 99%
“…1B). In addition to the ␣ 2 -DHPR, levels of the ␣ 1 -DHPR subunit, which is the major channel protein of the L-type voltage-dependent calcium channel, were assessed in TG S100A1 and NLC sarcolemmal membrane preparations by quantification of fluorescence DM-BODIPY-dihydropyridine binding (17). This revealed no significant difference between the groups (TG S100A1, 0.30 Ϯ 0.03 versus NLC, 0.31 Ϯ 0.06; n ϭ 6; p ϭ NS.…”
Section: Generation and Characterization Of S100a1 Transgenicmentioning
confidence: 99%